2007
DOI: 10.1038/nrc2127
|View full text |Cite
|
Sign up to set email alerts
|

Insights from transgenic mouse models of ERBB2-induced breast cancer

Abstract: One-third of patients with breast cancer overexpress the ERBB2 receptor tyrosine kinase, which is associated not only with a more aggressive phenotype but also reduced responsiveness to hormonal therapies. Over the past two decades, many ERBB2 mouse models for breast cancer have conclusively shown that this receptor has a causal role in breast cancer development. These mouse models have also enabled the mechanisms controlling tumour growth, angiogenesis, metastasis, dormancy and recurrence in ERBB2-positive br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
181
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(184 citation statements)
references
References 81 publications
2
181
1
Order By: Relevance
“…Gene amplification and overexpression of Neu/ErbB-2, a member of the epidermal growth factor receptor tyrosine kinase family, is found in 25-30% of primary breast cancer patients, who display a trend of early stage metastasis and poor survival rate (Slamon et al, 1987). These clinical observations have been clearly supported by the establishment of several Neu/ErbB-2-dependent transgenic models of breast cancer, showing a causal relationship between overexpression of Neu/ErbB-2 and the development of metastatic breast tumors (Muller et al, 1988;Siegel et al, 1994;Ursini-Siegel et al, 2007). In addition, it is becoming clear that Neu/ErbB-2-induced signaling pathways can be influenced by other signaling pathways leading to breast tumorigenesis.…”
Section: Introductionmentioning
confidence: 94%
“…Gene amplification and overexpression of Neu/ErbB-2, a member of the epidermal growth factor receptor tyrosine kinase family, is found in 25-30% of primary breast cancer patients, who display a trend of early stage metastasis and poor survival rate (Slamon et al, 1987). These clinical observations have been clearly supported by the establishment of several Neu/ErbB-2-dependent transgenic models of breast cancer, showing a causal relationship between overexpression of Neu/ErbB-2 and the development of metastatic breast tumors (Muller et al, 1988;Siegel et al, 1994;Ursini-Siegel et al, 2007). In addition, it is becoming clear that Neu/ErbB-2-induced signaling pathways can be influenced by other signaling pathways leading to breast tumorigenesis.…”
Section: Introductionmentioning
confidence: 94%
“…Neuroblastomas from these animals were shown to express a mutant ErbB2 homolog called neu. Since this discovery, a successful effort to generate mouse models of ErbB2-dependent breast cancer has informed our understanding of ErbB2/HER2/neu-dependent tumorigenesis [147]. Transgenic mice driving activated neu (neu-NT) expression within mammary epithelium under the mouse mammary tumor virus promoter (MMTV-neu-NT) rapidly develop mammary tumors within the entire mammary epithelium [148][149][150].…”
Section: Erbb Members In Diseasementioning
confidence: 99%
“…Recently, both in vitro and mouse studies have identified the disruption of β1 integrin function as a unique activator of cellular dormancy [40,41]. Inhibition of β1 integrin activity prevents tumor cell proliferation, but not cell viability, leading to the induction of a dormant state [42,43].…”
Section: Detachment-induced Autophagy and Tumor Cell Dormancymentioning
confidence: 99%